Authenticity is Contagious: Brand Essence and the Original Source of Production - Newman, George E.; Dhar, Ravi (Journal of Marketing Research, 2014)
It is well established that differences in manufacturing location can affect consumer preferences through lay inferences about production quality. In this article, the authors take a different approach to this topic by demonstrating how beliefs in contagion (the notion that objects may acquire a special aura or “essence” from their past) influence perceptions of authenticity for everyday consumer products and brands. Specifically, they find that due to a belief in contagion, products from a company's original manufacturing location are viewed as containing the essence of the brand. In turn, this belief in transferred essence leads consumers to view products from the original factory as more authentic and valuable than identical products made elsewhere. The authors further reveal that consumers who are higher in sensitivity to contagion are more likely to exhibit this effect and that activating the concept of contagion enhances preferences for products made in the brand's original factory. The authors close by discussing theoretical and practical implications of these findings.